Emergent landscapes of renewable energy storage: Considering just transitions in the Western United States. (August 2022) - Turley, Bethani; Cantor, Alida; Berry, Kate; Knuth, Sarah; Mulvaney, Dustin; Vineyard, Noel
Abstract: Governments, utilities, and energy companies are increasingly looking towards energy storage technologies to extend the availability of variable renewable power sources such as solar and wind. In this Perspective, we examine these fast-shifting developments by mapping and analyzing landscapes of renewable energy storage emerging across the Western United States. We focus on the rollout of several interrelated leading technologies: utility-scale lithium-ion batteries, supported by increasing regional lithium mining, and proposals for new pumped storage hydropower. Drawing on critical resource geography, we examine energy storage as both a component of renewable transition and as its own driver of landscape transformation, resource extraction, and conflict. By mapping and interpreting emerging Western landscapes, we show that leading energy storage technologies and the materials needed to make them can require extensive surficial land use and have significant regional water impacts, and that they are generating opposition from groups concerned about environmental degradation and (in)justice. We propose an agenda for future research on energy storage aimed at rendering its development more socio-ecologically beneficial and just.